8 - Le paradoxe de l’espace public dans la ville algérienne - Hadjidj, Djounid (Africa Development, 2021)
Through its multiple functions, the city creates its own standards of living that are defined in the specificity of the urban milieu, in contrast to the rural milieu, i.e. the creation of a new type of relationship, a different family structure, and new ways of living, working, consuming and dwelling. Through the multiple sociocultural, economic and political particularities it engenders, the city creates a change in traditionally prescribed relationships leading to the relaxing of social constraints, thereby imposing the coexistence of heterogeneous elements: a situation that unfailingly leads to conflicts between different individuals, cultures and groups. For many years, the city has been subjected to very numerous ‘in- flows’ of essentially rural population, little prepared, it is true, for a new urban lifestyle. This mass of country people that nurtured nostalgia for an illusion and had difficulty accepting indifference and detachment, ended up generating a new type of ‘city-dweller’, half-way between its rural roots that it has not shed, although they are increasingly denied by the new generations, and an urbanity to which everyone ardently as- pires. From this cultural duality arose the hybrid concept of the ‘rurban’. In this regard, it should be pointed out that, through a rapid and massive concentration of population with country roots, pauperized and weakened in the city, an inescapable and fast-growing phenomenon of ruralization of society has appeared. The ruralization of the city has changed the face of the urban space with a combination of modernity and tradition. Public space continues to be marked by the duality of the population, which attempts to make a place for itself in the city by occupying the social and economic terrain. Public space is taken here as a privileged space for the development of games and stakes that are continuously done and undone at the expense of the marginalized and destitute. The city retains this specificity due to the fact that it remains a melting- pot for creativity, where tradition and modernity are formed. The city is particularly distinguished by the original construction of the ‘Houma’ (neighbourhood) which is the public space par excellence where traditional life, based on morals, is perpetuated: respect for neighbours, decency, probity, … a space where social and community ties are redefined.